Decentralisation and functional specialisation in super mega-city regions: Changing functional patterns of manufacturing and knowledge-intensive business services activities in the polycentric super mega-city region of the Pearl River Delta - Feng, Pengfei; Growe, Anna; Shen, Yuming (ERDKUNDE, 2020)
This article deals with the processes of decentralisation and functional specialisation in the Chinese mega-city region of the Pearl River Delta (PRD). The PRD is one of the three largest mega-city regions and is the most polycentric of the three. Spatial changes in economic activities from 2000 to 2010 were analysed, based on occupational data. This analysis showed that, on one hand, the large centres are undergoing an upgrade and the range of occupations in formerly predominantly industrial centres has been expanded to include high-quality service occupations. On the other hand, decentralisation processes of economic activities in the hinterland were observed. In the formerly small economic centres in the hinterland, industrial activities, in particular, are on the increase. Service occupations continue to be concentrated in the large centres.